Combined inhibition of PI3Kδ and FLT3 signaling exerts synergistic antitumor activity and overcomes acquired drug resistance in FLT3-activated acute myeloid leukemia. (28th April 2018) - He, Ye; Sun, Liping; Xu, Yongping; Fu, Li; Li, Yun; Bao, Xubin; Fu, Haoyu; Xie, Chengying; Lou, Liguang
Abstract: PI3Kδ and FLT3 are frequently activated in acute myeloid leukemia (AML) and have been implicated as potential therapeutic targets. In this report, we demonstrate that combined inhibition of PI3Kδ and FLT3 exerts synergistic antitumor activity in FLT3-activated AML. Synergistic antiproliferative effects were observed in FLT3-activated MV-4-11 and EOL-1 AML cell lines, but not in FLT3-independent RS4;11 and HEL cells, as demonstrated by both pharmacological inhibition and silencing of PI3Kδ/FLT3. Combined treatment with PI3Kδ and FLT3 inhibitors more effectively inhibited AKT and ERK phosphorylation, and induced apoptosis more efficiently than either agent alone. This synergistic effect was confirmed in hematopoietic 32D cells transfected with an FLT3-ITD mutant, but not FLT3 wild type. In in vivo FLT3-activated AML xenografts, a PI3Kδ inhibitor CAL101 combined with FLT3 inhibitor led to significantly enhanced antitumor activity compared with either agent alone, in association with simultaneous inhibition of AKT and ERK. Importantly, CAL101 combined with FLT3 inhibitors overcame acquired drug resistance in FLT3-ITD AML cells. Thus, combined inhibition of PI3Kδ and FLT3 may be a promising strategy in FLT3-activated AML, particularly for patients with FLT3-inhibitor-resistant mutations. Highlights: Combined PI3Kδ and FLT3 inhibition exerts synergistic antitumor effects. Synergistic effects are achieved through enhanced inhibition of P-AKT and P-ERK. Combined PI3Kδ and FLT3 inhibition overcomes acquired drug resistance.